Spinning Religiously: A Study on the Predictive Power of Religiosity on Bahamian Online Gamblers’ Motivation and Intensity - Saunders, Christopher (International Journal of Bahamian Studies, 2020)
A survey of Bahamians explored the influence of the participant’s self-reported levels of religiosity on gambling behaviour. The study also investigated Bahamians’ motivations to participate in online games of chance. Results showed that religiosity was a significant predictor of motivations to not only attend these online games of chance but also the level in which these games were attended. The results are analysed in light of the uses and gratification paradigm while expanding the research into the connection of religiosity and gambling.